The Differential Experience and Educational Outcomes Among Two Cohorts of English Language Learning Students - Ngo, Hieu Van (Alberta Journal of Educational Research, 2023)
This study examined the differential experience and educational outcomes among two English Language Learning (ELL) student cohorts, namely holders of a high school diploma and individuals who did not complete high school. Our analysis of 39 interviews with ELL respondents demonstrated that premigration experience; personal qualities; interactions at home, in school, and in the community; as well as peer influence, have shaped the differing experience and inequitable educational outcomes of ELL students. The findings brought attention to the areas of support for all ELL students, including quality classroom instruction, explicit and structured ELL education, supplementary academic and literacy programs, responsive psychosocial support, and access to positive mentors. Keywords: ELL students, educational experience, educational outcome Cette étude a examiné les différentes expériences et résultats scolaires de deux cohortes d'étudiants apprenant l'anglais (ELL), à savoir les titulaires d'un diplôme d'études secondaires et les personnes qui n'ont pas terminé leurs études secondaires. Notre analyse de 39 entretiens avec des répondants ELL a démontré que l'expérience antérieure à la migration, les qualités personnelles, les interactions à la maison, à l'école et dans la communauté, ainsi que l'influence des pairs, ont façonné l'expérience différente et les résultats scolaires inéquitables des étudiants ELL. Les résultats ont attiré l'attention sur les domaines de soutien pour tous les étudiants ELL, notamment un enseignement de qualité en classe, une éducation ELL explicite et structurée, des programmes académiques et d'alphabétisation supplémentaires, un soutien psychosocial adapté et l'accès à des mentors positifs. Mots clés : étudiants ELL, expérience éducative, résultats scolaires